Effects of aerobic exercise on cardiac function and gene expression of NADPH oxidases in diaphragm muscle of rats with aortic stenosis-induced heart failure - Janini Gomes, Mariana; Sabela, Ana Karenina; Ferreira, Isabele Tiburcio Pecin; de Souza, Sérgio Luiz Borges [UNESP]; Mota, Gustavo Augusto Ferreira [UNESP]; da Silva, Vitor Loureiro [UNESP]; de Campos, Dijon Henrique Salomé [UNESP]; Lima, Aline Regina Ruiz [UNESP]; Carvalho, Marianna Rabelo; Bazan, Silmeia Garcia Zanati [UNESP]; Corrêa, Camila Renata [UNESP]; Cicogna, Antônio Carlos [UNESP]; et al. (Frontiers, 2023)
We evaluated the influence of aerobic physical exercise (EX) on gene-encoding proteins associated with oxidative stress in diaphragm muscle of rats with aortic stenosis-induced heart failure (HF). Wistar male rats were divided into four groups: Control sedentary (C); Control exercise (C-Ex); Sedentary aortic stenosis (AS); Aortic stenosis exercise (AS-Ex). Exercised rats trained 5 times a week for 10 weeks on a treadmill. Statistical analysis was performed by ANOVA or Kruskal–Wallis test. In the final echocardiogram, animals with aortic stenosis subjected to exercise demonstrated improvement in systolic function compared to the sedentary aortic stenosis group. In diaphragm muscle, the activity of antioxidant enzymes, malondialdehyde malondialdehyde concentration, protein carbonylation, and protein expression of p65 and its inhibitor IκB did not differ between groups. Alterations in gene expression of sources that generate reactive species of oxygen were observed in AS-Ex group, which showed decreased mRNA abundance of NOX2 and NOX4 compared to the aortic stenosis group (p < 0.05). We concluded that aerobic exercise has a positive impact during heart failure, ameliorating systolic dysfunction and biomarkers of oxidative stress in diaphragm muscle of rats with aortic stenosis-induced heart failure.
Keywords: aerobic physical exercise; aortic stenosis; diaphragm; heart failure; oxidative stress